Appearance matters: sedimentation effects on different sponge morphologies. (16th January 2015) - Pineda, M. Carmen; Duckworth, Alan; Webster, Nicole
Abstract : Dredging activity poses an environmental risk to sponges as sediments from the dredge or disposal site may smother the sponge surface, potentially affecting water filtration and light penetration. Dredge-related sedimentation effects may also vary between sponge morphologies, potentially impacting community structure and functioning. To test this, 10 sponge species encompassing four different morphologies (massive, erect, cup and encrusting), were exposed to a single pulse treatment of three different sediment concentrations (0, 250 and 500 mg l −1 ) and followed over 2 weeks, in 1000 l tanks. Total suspended solids (TSS) and sedimentation rates (SR) were recorded throughout the study. A sharp decrease in TSS was recorded within the first 2–3 h and a total settlement of sediments occurred within the first 48 h of the pulse exposure (0, 8 and 16 mg cm −2 in the control, medium and high sediment treatments, respectively). The effects of high sedimentation included mortality of cup-shaped Callyspongia confoederata and small areas of tissue necrosis in other species, with massive, encrusting and wide cup morphologies particularly affected. However, the sediment concentrations tested in this experiment did not cause changes in the concentration of sponge pigments or the structure of the symbiotic microbial community in any species. These results indicate that a single pulse of sediments less than 16 mg cm −2 is not detrimental to most of the sponge species studied.